Literature Review Study: Factors Affecting Caring Performance in Low Birth Weight (LBW) Infants - Ira Rahmawati; Rahmawati, Iis; Alfarizi, Muhammad (Nursing and Health Sciences Journal (NHSJ), 2024)
Globally, neonatal deaths are caused by LBW during home care. Complex LBW care when returning home requires parental knowledge and skills in understanding the baby's condition. Good care performance is required by parents and controlling factors that influence treatment at home. This study aimed to identify the factors that influence caring performance in LBW. The study using a literature review narrative design with 4 stages of selection based on the PRISMA diagram. Articles were searched using the search engines PubMed, SpringerLink, ScienceDirect, and Google Scholar with Indonesian and English keywords. From the results of the review, 11 articles were obtained which contained factors that influence caring performance during home care. From the analysis of all articles, it was found that there were 4 factors that influenced caring performance, namely maternal factors, sociodemographic factors, external factors, and cultural factors. The factor that has the most influence on caring performance is the mother's factor. Special interventions are needed for mothers to improve skills in LBW care at home to reduce neonatal mortality.